Development Of An Indirect Elisa Using The Recombinant Nucleocapsid Protein As Antigen For Detection Of Antibodies To Newcastle Disease Virus - Md Saad, Norsharina (2007)
Newcastle disease (ND) is a virulent form of poultry disease that has the potential to cause 100% mobidity and mortality. The continuing threat of ND to the poultry industry requires routine testing of vaccinated chickens to determine that they have been adequately immunised by vaccination. Enzyme-linked immunosorbent assays (ELISA) which use commercially available reagents are presented as alternatives to the procedure for detection of Newcastle disease virus (NDV) antibodies. The nucleocapsid protein has been shown to immunogenic in nature, and play key roles in diagnostic ELISA for detection of antibody. A purified recombinant nucleocapsid protein (NP) of NDV highly expressed in Escherichia coli (E. coli) was used as the coating antigen in an indirect ELISA to detect the presence of NDV antibodies in a cohort of chicken sera. The test was standardised using sera from vaccination study and obtained from Charles River SPAFAS Laboratories, USA. The NPELISA was standardised at an antigen concentration of 1.5 μg/ml, test serum dilution of 1:200 and conjugate dilution of 1:2000. The cut-off value of the NP-ELISA of 0.238 was determined by a receiver operating characteristic (ROC) analysis. An assay of 315 chicken serum samples against NDV antibodies showed that the NP-ELISA had 92.06% sensitivity and 93.2% specificity compared to NDV hemagglutination–inhibition (HI) test. This was in good agreement between the two serological methods (κ =0.848). In the serum neutralization test (SNT), the result shows that there was no correlation observed between HI and SNT. It was observed that the field serum samples found positive or with high titer in the HI test were negative or have low titer for SNT. This suggests that different epitopes on the antigen have been recognized by each of the tests. The result shows that the recombinant NP antigen is recognized by antibodies specific to the other poultry pathogens and the cross reactivity is high for Paramyxovirus-2 (PMV-2) and Paramyxovirus-3 (PMV-3) but low reaction by other poultry pathogen [avian influenza (AI), avian encephalomyelitis (AE), infectious laryngotracheitis (ILT), infectious bronchitis (IB), and infectious bursal disease (IBD)]. The titre of ND antibodies can be determined using NPELISA formula, Log10Titre = 1.0* Log(S/P) + 3.45. This formula was derived after getting the linearity graph between NP-ELISA to commercial ND test kit. This finding indicates the potential application of the E. coli produced NP protein as antigen in indirect ELISA for the detection of NDV antibody. The NP-ELISA was successfully developed and very useful which is more or as efficient as commercial kits, thus the cost of NP-ELISA is cheaper than commercial kits.